Utilizing Learning Media In Biology: A Step Towards Interactive Media Development - Putri, Iffa Ichwani; Rahmat, Adi; Riandi, Riandi; Riza, Lala Septem (Journal of Natural Science and Integration, 2024)
The study addresses the complexities inherent in teaching and learning biology, a subject that is often challenging for students due to its intricate concepts. Focusing on the intersection of pedagogy and technology, this research evaluates the perceptions of high school teachers and students towards the integration of contemporary learning media in biology instruction. Utilizing a descriptive and quantitative approach, the research engaged a purposively sampled cohort of educators and learners to explore their views. this study involved 56 teachers and 133 students spread across several schools. Data were gleaned through a combination of structured questionnaires and interviews, subsequently subjected to quantitative analysis. The findings reveal a consensus on the critical role of media in facilitating biology education. Teachers and students agree that technology-based media can improve understanding of biological concepts and strengthen student engagement. While there is a significant reliance on media to convey biological concepts, the findings indicate that the potential of technology-based media. However, the study uncovers a lag in the effective deployment of technological resources, with interactive multimedia being underutilized by a notable fraction of educators. This gap underscores the need for enhanced strategies to foster the adoption of technology-enhanced learning tools in the biological sciences.Keywords: interactive, multimedia, science, technology